PERAN APLIKASI SISTEM KEUANGAN DESA TERHADAP KINERJA PEMERINTAH DESA DENGAN BUDAYA ORGANISASI SEBAGAI PEMEDIASI - Temalagi, Selva; Kalorbobir, Yohana Magdalena (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
Basically, the performance of village officials is greatly influenced by the individual's internal conditions which arise from their background, skills, abilities and motivation, as well as the individual's external conditions which are often called situational factors. Situational factors include management, work environment, task complexity, social or co-worker relationships, and internal culture within the organization. As information technology develops, every village is required to carry out financial reports on the village financial system application provided by BPKP. This study aims to test and analyze the influence of village financial system applications on government performance with organizational culture as a mediator. The results of this study found that the village financial system had a positive and significant effect on village government performance and organizational culture, and organizational culture had a positive and significant effect on village government performance. However, organizational culture cannot mediate the influence of the village financial system on village government performance. This study has the implication that the application of a village financial system can help villages to improve village government performance.